Perception Convenience, Price, Promotion and Brand Image Satisfaction Customer GrabBike in Samarinda City - Aksenta, Almasari; Syachrul; Audhis, Allayza (International Journal of Economic, Finance and Business Statistics, 2024)
This research is quantitative research and aims to determine the influence of variables of perception convenience, price, promotion and image brand to GrabBike customer satisfaction in Samarinda City.​ This research was collected through questionnaire to 100 respondents in Samarinda City which was obtained through nonprobability sampling sample technique with determination of purposive sampling. The data analysis technique used multiple regression analysis. The results of this study indicate that the variables price, promotion and brand image have a significant effect on customer satisfaction, while the perceived ease variable does not have a significant effect.